Disruption of the murine interleukin-4 gene inhibits disease progression during Leishmania mexicana infection but does not increase control of Leishmania donovani infection. - Satoskar, A (1995)
The growths of both cutaneous leishmaniasis and visceral leishmaniasis caused by Leishmania mexicana and Leishmania donovani, respectively, were measured in interleukin-4 (IL-4) knockout mice (IL-4-/-) and compared with those of similarly infected wild-type (IL-4+/+) control mice. While large, nonhealing, cutaneous lesions containing large numbers of parasites developed in IL-4+/+ mice subcutaneously infected with 5 x 10(6) L. mexicana amastigotes in the shaven rump, in IL-4-/- mice no lesions whatsoever developed and parasites were difficult to detect. Systemic spread and metastasis were also noted in IL-4+/+ but not IL-4-/- mice. In contrast, IL-4-/- mice infected intravenously with 10(7) L. donovani amastigotes were found to have consistently higher parasite burdens in their livers throughout infection than did their wild-type counterparts. However, these differences were only significant at 15 days postinfection. While the results reported here pertaining to L. donovani largely support previous studies, those related to L. mexicana provide new observations. The immunological responses of IL-4-/- and IL-4+/+ mice infected with L. mexicana were, therefore, examined both in vivo and in vitro. Although neither IL-4-/- nor IL-4+/+ mice infected with L. mexicana produced parasite-specific immunoglobulin G2a antibodies, IL-4+/+ mice, unlike IL-4-/- mice, developed significant immunoglobulin G1 antibody titers as infection progressed, indicating a Th2-influenced response in wild-type mice. In addition, IL-4-/- mice, unlike IL-4+/+ mice, developed a significant delayed-type hypersensitivity response, indicating a Th1-influenced response in IL-4-/- mice. Following in vitro stimulation, splenocytes from IL-4+/+ mice infected with L. mexicana displayed significantly higher antigen-specific proliferative responses than did IL-4-/- mice. However, gamma interferon production as measured from the supernatants of the in vitro splenocyte cultures of IL-4-/- mice was significantly higher than that from IL-4+/+ mice. This again would indicate a predominantly Th1-influenced response in the absence of a Th2 response in IL-4-/- mice infected with L. mexicana. On the other hand, at the same time point, draining lymph node cells from IL-4+/+ mice produced significantly higher quantities of IL-5 than did those from IL-4-/- mice following in vitro antigenic stimulation.(ABSTRACT TRUNCATED AT 400 WORDS)